Estudo anatômico do ligamento meniscotibial medial do joelho: análise histológica da estrutura de colágeno e vascularização - Santos, Amanda Progenio dos (2024)
Anterior cruciate ligament (ACL) rupture is the most common ligament injury of the knee. When associated with medial meniscotibial ligament (MMTL) injury, greater joint instability is observed. Therefore, MMTL repair is currently recommended at the same surgical time as ACL reconstruction to reduce the risk of ACL re-rupture. Although the MMTL has been described macroscopically in anatomical dissections, little is known about its structural characteristics in terms of collagen fibers and microvascularization. The objective of this study was to describe the collagen matrix structure and vascularization of the MMTL to contribute to the refinement of the surgical technique for repair of these structures during arthroscopy and consequently lead to a decrease in failure. Twelve MMTLs from six fresh cadavers were collected. Macroscopic morphometric measurements and histological analysis were performed using Hematoxylin and Eosin staining. The collagen matrix was evaluated using Picrosirius red staining under polarized light microscopy, and for microvascularization analysis, an immunohistochemical technique with a commercial antibody against the endothelial antigen CD31 was used. Of the total samples, 83.3% of the ligaments were from male cadavers and 16.7% from female cadavers. In the intrasubstancial portion of the ligament, collagen fibers were observed to be arranged in an organized manner, and in the meniscal insertion portion, the presence of adipose tissue was observed with increased local cellularity compared to the intrasubstancial portion. The analysis of the collagen matrix showed a type I to type III collagen ratio of 3.86 (±3.07). The mean microvascular density in the intrasubstancial portion was 33.71 ± 8.7 vessels/mm² and in the meniscal insertion portion was 74.14 ± 23.85 vessels/mm². The MMTL is a structure formed by oriented and parallel collagen fibers, with low cellularity in its intrasubstancial portion and with increased cellularity near the meniscal insertion, especially due to the greater presence of microvessels in this region. Type I collagen predominates over type III collagen, and microvascular density is high in the meniscal insertion region. However, vascularization is scarce in the intrasubstancial region, directly impacting the healing potential of ramp lesions since these lesions occur in this region.